Dakwah Kultural Berbasis Kearifan Lokal - Ahmadi, Mubarok; Baharuddin, Razif (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Local traditions play an important role in delivering religious messages that are contextual and inclusive in the global era. The Jaran Jenggo tradition, a regional performance accompanied by Islamic musical elements, is rich with da'wah values. This study aims to analyze the forms of da'wah communication that emerge in Jaran Jenggo performances, identify the Islamic values represented, and examine community perceptions of the da'wah messages conveyed. The research employs a descriptive ethnographic approach through field observation, interviews, and performance documentation. The results show that da'wah communication in the Jaran Jenggo tradition is manifested through symbolic movements, Islamic musical expressions, and social interactions between performers and audiences. Values of tawakal (trust in God) and mutual respect are represented in each scene. The community perceives that da'wah delivered through Jaran Jenggo is more easily accepted because it fosters familiarity with their own culture and creates harmony between religious and local values.